Faktor-Faktor Yang Mempengaruhi Tingkat Kepuasan Pasien Rawat Inap Terhadap Pelayanan Keperawatan Di Poliklinik Rumah Sakit Kasih Ibu Tabanan - I Nyoman Gede Bayu Wiratama Suwedia; Nyoman Tri Maryanthi; Ni Putu Indah Rosita (Bajang Institute, 2026)
Background: Patient satisfaction is a key indicator of hospital service quality, influenced by the quality of nursing care. Despite various quality improvement efforts, complaints regarding nurse responsiveness, communication, and other service aspects persist, potentially diminishing patient satisfaction at Kasih Ibu Tabanan Hospital. Objective: This study aimed to analyze the factors influencing the satisfaction levels of inpatients regarding nursing care at the Polyclinic of Kasih Ibu Tabanan Hospital. Method: A quantitative study using a cross-sectional analytic survey design was conducted from April to May 2025. A total enumeration sampling technique was employed, involving 109 inpatients. Independent variables included responsiveness, competence, tangibles, communication, and reliability, while the dependent variable was patient satisfaction. Data were collected using a validated and reliable questionnaire and analyzed via univariate, bivariate (Chi-Square test), and multivariate (logistic regression) methods. Results: A total of 59.6% of respondents expressed satisfaction with the nursing care. Bivariate analysis revealed that responsiveness (p<0.001), competence (p=0.032), communication (p=0.003), and reliability (p=0.047) were associated with patient satisfaction, whereas tangibles were not (p=0.485). Multivariate analysis indicated that responsiveness (aOR=3.96; 95% CI=1.64–9.53; p=0.002) and communication (aOR=2.61; 95% CI=1.09–6.26; p=0.032) significantly influenced patient satisfaction, with responsiveness being the dominant factor. Conclusion: Nurse responsiveness and communication are the primary factors influencing inpatient satisfaction. Therefore, the hospital needs to prioritize enhancing nurses' competence in responsiveness and communication to improve service quality and patient satisfaction.